2015
DOI: 10.1186/s13012-015-0302-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to reporting adverse drug events in hospitals: a qualitative study using theoretical domains framework approach

Abstract: BackgroundAdverse drug events (ADEs) are a major source of morbidity and mortality, estimated as the forth to sixth cause of annual deaths in the USA. Spontaneous reporting of suspected ADEs by health care professionals to a national pharmacovigilance system is recognized as a useful method to detect and reduce harm from medicines; however, underreporting is a major drawback. Understanding the barriers to ADE reporting and thereafter design of interventions to increase ADE reporting requires a systematic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 36 publications
6
61
0
Order By: Relevance
“…The TDF has been used to identify barriers to implementing a range of practices with implications for patient safety including reporting adverse drug events in hospitals [46], reducing prescribing errors among trainee doctors [47], preventing misplaced nasogastric feeding tubes [44, 45], implementing stroke guideline recommendations [48], and encouraging hand hygiene practices [33]. …”
Section: Introductionmentioning
confidence: 99%
“…The TDF has been used to identify barriers to implementing a range of practices with implications for patient safety including reporting adverse drug events in hospitals [46], reducing prescribing errors among trainee doctors [47], preventing misplaced nasogastric feeding tubes [44, 45], implementing stroke guideline recommendations [48], and encouraging hand hygiene practices [33]. …”
Section: Introductionmentioning
confidence: 99%
“…Activities to improve the understanding and awareness of pharmacovigilance have been underway in Turkey since 2008, when a similar study to our own conducted in Istanbul, Turkey indicated "an urgent need for educational programs to train them about pharmacovigilance and ADR reporting. " which is a common problem faced by many countries [11][12][13]. The rates and attitudes towards ADR reporting, training programs should be improved for safety of public health.…”
Section: Resultsmentioning
confidence: 99%
“…ADRs reporting rate may be increased by overcoming the barriers because some of them can be solved through proper management and advertising of pharmacovigilance program such as distribution of reporting forms and appropriate guidelines hence making them widely available. The study by Mirbaha et al, identified six domains as relevant to barriers of ADRs reporting in hospitals [19]. These domains included some of the barrier observed in the current study such as "Knowledge", "Motivational factors and teamwork", Nonetheless, creating a closer relationship between nurses and ADRs reporting centers, providing nurses with proper reading materials as references to help them identify occurrence of adverse drug reactions, these can enormously enhance reporting performance.…”
Section: Discussionmentioning
confidence: 99%